Desempenho de um sistema para gerenciamento de projetos de software qual a influência da maturidade organizacional?: um estudo de caso no Serviço Federal de Processamento de Dados (Serpro) - Santos, Fabio Brito (2010)
This thesis evaluates the extent to which the performance of an information system for managing software projects depends on the organizational maturity in project management, as the perception of analysts who play the role of leaders / managers of the segment in focus. The field research of this work is supported by a literature review on the following topics: project management software, evaluation of management information systems; success factors in information systems, and finally maturity in project management and its impact on systems project management. A research was done through a survey in SERPRO, public company data processing with offices in every capital of Brazil, and the sample was composed of officials from the sectors of software development. The results were analyzed with descriptive analysis, associations and correlations between variables: performance of a system of project management software, measured by user satisfaction and maturity in project management. In conclusion, the data analysis, that certain areas of organizational maturity in project management exert some influence on the performance of the system of project management used and users more satisfied with such a system have a greater sense of maturity.